Studi Optimasi Peningkatan Kekuatan Bending Komposit Berpenguat Serat Nanas-Nanasan (Bromeliaceae) Kontinu Searah - Rahman, Muh Budi Nur; Suwanda, Totok; Diharjo, Kuncoro (Semesta Teknika, 2008)
The objectives of this research are to observe the bending strength composite with bromeliaceae fiber with variations of alkali treatment duration, variations of fiber fraction volume and to observe the broken section characteristics. Materials used are bromilicea fiber, resin polyester, NaOH alkali and distilled water. The composite made with printing press methods. Dimensions of specimens and bending testing methods is done by to the standard ASTM D790 (bending test). Variables in this research are fiber fraction volume in the amount of 20-50% and the soaking times in alkali treatment are 0, 2, 4, 6 and 8 hours. Visualization of the broken section is shown in the macro picture. Highest bending strength and bending tensile occur in the composite with bromeliaceae fiber for 6-hour alkali treatment of 218.06 MPa and at the amount of 4.39% in fraction volume of 34.96%. Highest bending modulus occurs with 4 hours alkali treatment of 5.92% GPa. Composite with bromeliaceae fiber without alkali treatment has broken section characteristics fiber pull out, but the composite with alkali treatment has less fiber pull out characteristics.